Problems of Mediation by Religious Court Judges in Lampung Province - A. Kumedi Ja’far; Erik Rahman Gumiri; Edi Susilo (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
This article discusses the problems surrounding mediation by Religious Court judges in Lampung Province. Mediation can help simplify a dispute so that it can be resolved more cheaply and quickly. Interestingly, mediation allows litigants to find their solutions or settlements, expecting each party to be satisfied and fairly treated. However, this is not the case in real life. Mediation implementation falls short for a variety of reasons. The results of this study show that the mediation carried out by judges at the Religious Court of Lampung has several problems. Judges are unable to provide optimal mediation in divorce cases because mediation is frequently carried out in their respective homes by religious or traditional leaders. As a result, when mediation takes place in court, the mediation is less than optimal, and the divorce process is thought to be complicated or prolonged. Because not all judges hold mediator certificates, their ability to conduct mediation remains limited. When acting as mediators, some judges appear to be trial judges instead of judges who have received mediator training. Policies such as 'one-day minutes, one-day publish' indirectly impact the performance of judge mediators, despite some Religious Courts setting aside special time for mediation. Artikel ini membahas tentang permasalahan mediasi yang dilakukan oleh hakim Pengadilan Agama di Provinsi Lampung. Mediasi dapat membantu menyederhanakan suatu sengketa sehingga dapat diselesaikan dengan lebih murah dan cepat. Menariknya, mediasi memungkinkan para pihak yang bersengketa untuk menemukan solusi atau penyelesaiannya, dengan harapan masing-masing pihak merasa puas dan diperlakukan secara adil. Namun, kenyataan di lapangan tidak demikian. Pelaksanaan mediasi tidak berjalan dengan baik dengan berbagai penyebab.. Hasil penelitian ini menunjukkan bahwa mediasi yang dilakukan oleh hakim Pengadilan Agama Lampung memiliki beberapa permasalahan. Hakim tidak dapat memberikan mediasi yang optimal dalam perkara perceraian karena mediasi sering kali dilakukan di rumah masing-masing oleh tokoh agama atau adat. Akibatnya, ketika mediasi dilakukan di pengadilan, mediasi menjadi kurang optimal, dan proses perceraian dianggap rumit atau berlarut-larut. Karena tidak semua hakim memiliki sertifikat mediator, maka kemampuan mereka dalam melakukan mediasi pun menjadi terbatas. Ketika bertindak sebagai mediator, beberapa hakim tampak seperti hakim pengadilan, bukan hakim yang telah mendapatkan pelatihan mediator. Kebijakan seperti 'one-day minutes, one-day publish' secara tidak langsung berdampak pada kinerja mediator hakim, meskipun beberapa Pengadilan Agama menyediakan waktu khusus untuk mediasi.